Impact of source of infection and vancomycin AUC0–24/MICBMD targets on treatment failure in patients with methicillin‐resistant Staphylococcus aureus bacteraemia. (12th July 2014) - Ghosh, N.; Chavada, R.; Maley, M.; van Hal, S. J.; Mainardi, J.‐L.
Abstract Despite recent controversies about toxicity and reduced efficacy, vancomycin remains the current treatment of choice for methicillin‐resistant Staphylococcus aureus (MRSA) bacteraemia. The parameter associated with treatment success is the vancomycin 24‐h area under concentration‐time curve to MIC ratio (AUC0–24/MIC). We aimed to determine the utility of calculated AUCs and explore the optimal AUC0–24/MIC targets associated with treatment success. In this single‐centre retrospective observational cohort study of 127 patients with MRSA bacteraemia, forty‐five (35.4%) did not respond to vancomycin treatment. Patient characteristics were essentially the same between those who did not respond to vancomycin treatment and those with treatment success, with independent predictors of treatment failure being source of bacteraemia (odds ratio (OR), 4.29; 95% confidence interval (CI), 1.50–12.26; p 0.007) and not achieving an AUC0–24/MICBMD (using broth microdilution) target of ≥398 (OR, 11.4; 95% CI, 4.57–28.46; p< 0.001). Bacteraemic source‐specific thresholds were observed with a higher AUC0–24/MICBMD target of 440 required for high‐risk sources (e.g. infective endocarditis) compared with 330 for low‐risk sources (line related bacteraemia). Overall treatment success in patients with MRSA bacteraemia was associated with a vancomycin AUC0–24/MICBMD target of ≥398, with source‐specific targets observed. Future vancomycin practice guidelines will need to take into account MIC methodology, source of bacteraemia and patient populations prior to setting targets and monitoring recommendations.